K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 10 2019

x^2 -(a+b)*xy +aby^2

=x^2- axy -bxy+aby^2

= x(x-ay) - by(x-ay)

=(x-by)(x-ay)

6 tháng 10 2019

thanks

x+y+1=0 suy ra x+y=1

Làm câu A nhé B,C tương tự

A= x^2.(x+y-2)-(xy+y^2-2y)+(y+x-1)=0-y.(x+y-2)+1=1

Hok tốt

xin lỗi nha x+y=-1 nhé

\(A+B=2x^2y+x^2-1\)

\(A-B=-2xy^2+5x^2+1\)

\(A+B=2x^2y+x^2-1\)

\(A-B=-2xy^2+5x^2+1\)

19 tháng 7 2018

1)   \(x^3+y^3+z^3-3xyz\)

\(=\left(x+y\right)^3+z^3-3xy\left(x+y+z\right)\)

\(=\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-zx\right)\)

3)  \(ab\left(x^2+y^2\right)+xy\left(a^2+b^2\right)\)

\(=abx^2+aby^2+a^2xy+b^2xy\)

\(=ax\left(bx+ay\right)+by\left(ay+bx\right)\)

\(=\left(ay+bx\right)\left(ax+by\right)\)

19 tháng 7 2018

4)  \(-12x^4y+12x^3y^2-3x^2y^3\)

\(=-3x^2y\left(4x^2-4xy+y^2\right)\)

\(=-3x^2y\left(2x-y\right)^2\)